Discourse markers in the speech of Italian tourist guides: a corpus-based study - Alfano, Iolanda (Círculo de Lingüística Aplicada a la Comunicación, 2025)
The aim of this paper is to illustrate the incidence and functions of Discourse Markers (DMs) in the speech of tourist guides (TGs), and further investigate their polyfunctionality. Approximately 3½ hours of speech were examined (corresponding to 30,429 graphic words). These consisted of audiovisual recordings of Neapolitan expert guides conducting guided tours of the San Martino Charterhouse (Naples), extracted from the CHROME Corpus (Origlia et al., 2018; Alfano et al., 2023). A total of 1759 occurrences were analyzed. DM functions were studied by means of an onomasiological approach considering interactional, metatextual and cognitive dimensions, and then annotated using a multilevel annotation scheme. The examined features concern frequency, variability in forms, the possibility of co-occurrence and polyfunctionality, on both the syntagmatic and the paradigmatic axes. The results show that DMs are powerful indicators of the type of register: their functional distribution responds to specific communicative needs and the choice of preferred DMs depends very much on their polyfunctionality: the more polyfunctional they are, the more frequent they are likely to be. Finally, polyfunctional clusters of DMs do not present restrictions with respect to functions, whereas monofunctional clusters of DMs tend to appear with a planning or focusing function.